Tunable surface-plasmon-polariton filter constructed by corrugated metallic line and high permittivity material - Luo, Jiang (2018)
This paper presents the development of a novel surface plasmon polariton band-stop filter with tunable operating frequency. The tuning is done by embedding a high permittivity BST dielectric block into the gap of SPP transmission line (T-line). An obvious transmission dip at the certain frequency is observed due to Fabry-Pérot interference. The notch frequency is sensitive to the variation of the dielectric constant of the BST ceramic. Specifically, a transmission dip up to -11.5 dB is observed at the notch frequency of 8.12 GHz when the dielectric constant of BST is 425; the notch frequency shifts from 8.7 to 7.6 GHz when the dielectric constant of BST increases from 375 to 475. To further verify the functions of the proposed SPP filter, a prototype is fabricated on the Rogers-4003 dielectric substrate. The measured and the simulated results show good agreements. The proposed structure has outstanding features of a very compact area, simple fabrication, and tunable operating frequency, which have great potential for the applications in tunable frequency selection metamaterials devices.